若f(x)=sinα-cosx,则f′(α)=______.
举一反三
- 若f(x)dx=F(x)+C,则sinf(cosx)dx等于() A: F(sinx)+C B: -F(sinx)+C C: F(cosx)+C D: -F(cosx)+C
- 若f(x)的一个原函数的cosx,则∫f’(x)dx=______。
- 设f(x)=cosx,则f(-cosx)=______.
- 17e0b849d3a4a3b.jpg,计算[img=19x34]17e0ab14a855463.jpg[/img]的实验命令为( ). A: syms x; f=diff((1+sin(x)^2)/cos(x),1)f=2*sin(x) + (sin(x)*(sin(x)^2 + 1))/cos(x)^2 B: f=diff((1+sinx^2)/cosx,1)f=1/2/x^(1/2)/(1-x)^(1/2) C: syms x;f=diff((1+sinx^2)/cosx,1)f=2*sin(x) + (sin(x)*(sin(x)^2 + 1))/cos(x)^2
- 若∫f(x)dx=F(x)+C,则∫cos xf(sin x)dx等于______. A: F(sin x)+C B: -F(sin x)+C C: F(cos x)+C D: -F(cos x)+C